Forage Sorghum Silage Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C.; Duncan, Stewart R. (My University, 2001)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_2001_10
Keywords: MF648; Economics; Crops; MF